The influence of the people’s will in Constitutional Interpretation. An abuse of vague legal concepts? - Emilio J. Urbina Mendoza (Estudios de Deusto, 2014)
The assumption of a new concept in interpretive processes undertaken since 1999 by the Supreme Court in its Constitutional Chamber Venezuela have been built in a sequence of criteria which, all constitutional judges must heed the call of the popular will as north hermeneutic in all areas of legal knowledge. This popular constitutional interpretation has chased an alternative judicial discourse confronted with logic and the Western legal tradition, permeating categories and definitions little or nothing is set in the vocabulary or the theory of law. In 2007, with the failed constitutional reform, sought to impose as interpretive guideline popular supremacy. However, in the 48 presidential decree-laws, 2008, imposed the concept of “public interest” as the judge directed anchoring constitutional hermeneutic, and thus, warped the very essence of the concept called “vague legal concepts”. Published online: 05 December 2014